Activating a/r/tographic propositions: Walking with art education. Issue 2 (1st August 2021) - Sinner, Anita; Irwin, Rita L.
For your purposes as an art educator, how do you define 'art' and 'artist'? Some critics argue that, in today's art world, the 'institutional' definition of art reigns. What other definitions of art seem credible and useful to you as an art educator?